Addressing psychological, mental health and other behavioural healthcare needs of the underserved populations in the United States: the role of local health departments. (March 2016) - Shah, Gulzar H; Luo, Huabin; Winterbauer, Nancy; Madamala, Kusuma
Aims: (1) To assess the extent to which local health departments (LHDs) implement and evaluate strategies to target the behavioural healthcare needs for the underserved populations and (2) to identify factors that are associated with these undertakings. Methods: Data for this study were drawn from the 2013 National Profile of Local Health Departments Study conducted by National Association of County and City Health Officials. A total of 505 LHDs completed the Module 2 questionnaire of the Profile Study, in which LHDs were asked whether they implemented strategies and evaluated strategies to target the behavioural healthcare needs of the underserved populations. To assess LHDs' level of engagement in assuring access to behavioural healthcare services, descriptive statistics were computed, whereas the factors associated with assuring access to these services were examined by using logistic regression analyses. To account for complex survey design, we used SVY routine in Stata 11. Results: Only about 24.9% of LHDs in small jurisdiction (<50, 000 population) and 35.3% of LHDs in medium-size jurisdiction implemented/evaluated strategies to target the behavioural healthcare services needs of underserved populations in their jurisdiction in 2013. Logistic regression model results showed that LHDs having city/multicity jurisdiction (adjusted odds ratio (AOR) = .16, 95% confidence interval (CI): .04–.77), centralised governance (AOR = .12, 95% CI: .02–.85), and those located in South Region (AOR = .25, 95% CI: .08–.74) or the West Region (AOR = .36, 95% CI: 14–.94), were less likely to have implemented/evaluated strategies to target the behavioural healthcare needs of the underserved. Conclusions: The extent to which the LHDs implemented or evaluated strategies to target the behavioural healthcare needs of the underserved population varied by geographic regions and jurisdiction types. Different community needs or different state Medicaid programmes may have accounted for these variations. LHDs could play an important role in improving equity in access to care, including behavioural healthcare services in the communities.